Registration of 'WyoWinter' Feed Pea for the US Central Great Plains. Issue 2 (11th April 2019) - Homer, A.; Islam, M. A.; Krall, J. M.; Nachtman, J. J.; Groose, R.W.
Abstract : 'WyoWinter' (Reg. No. CV‐29, PI 688001; experimental designation Wyo #11) is a winter feed pea [ Pisum sativum L. ssp. sativum var. arvense (L.) Poir.] developed by the University of Wyoming and the Wyoming Agricultural Experiment Station and released in 2016 for its adaptation and high forage and seed yield in Wyoming. WyoWinter was derived from a cross between a selected late‐flowering plant of landrace Austrian Winter and a late‐flowering plant of landrace Common Austrian Winter. WyoWinter traces back to a single F2 plant grown in a spaced‐plant nursery and was developed by a combination of pedigree and bulk breeding methods. WyoWinter was evaluated in fall‐sown yield trials in 2 yr, two locations, and two growing conditions (dryland and irrigated). Over 2 yr and two locations, forage yield of WyoWinter averaged 694 and 2739 kg ha −1 and seed yield averaged 954 and 2249 kg ha −1 under dryland and irrigated conditions, respectively. WyoWinter has indeterminate growth habit, and seed has yellow cotyledons and pigmented seed coat. The 1000‐seed weight was 110 g. Forage nutritive values were high and comparable to check cultivars. WyoWinter exhibits excellent winterhardiness and good performance in southeast Wyoming and northwest Nebraska. It can be used as a forage crop, as grain for livestock feed, and as a green manure or cover crop. WyoWinter has potential to be integrated as a rotational crop in the winter wheat ( Triticum aestivum L.)–summer fallow farming system in the central Great Plains.